First observation of histopathological effects of 2,4,6-trinitrotoluene (TNT) in gills of European eel Anguilla anguilla (Linnaeus, 1758) - SENSINI C; DELLA TORRE, CAMILLA; CORSI, ILARIA; FOCARDI, SILVANO ETTORE (Cell Biology and Toxicology, 2008)
The aim of the present study was to investigate the effects on gill morphology of the explosive 2,4,6-trinitrotoluene (TNT) in a model fish, the European eel, Anguilla anguilla (Linnaeus, 1758) to assess potential detrimental effects in marine fish due to its presence in dumping areas. Juvenile specimens of A. anguilla were exposed in vivo for 6 and 24 h to 0.5, 1 and 2.5 mg/l nominal concentrations of TNT using dimethyl sulfoxide (0.1 parts per thousand) as solvent carrier. Histological analysis of gills indicated that TNT induced several structural lesions. After 6h of exposure at 0.5 and 1 mg/l TNT, oedema of some secondary lamellae was evident: this change at the highest dose of 2.5 mg/l led to epithelial lifting and detachment from the endothelium and rupture of the branchial membrane and vascular congestion. After 24 h at 0.5 mg/l, increased oedema in secondary lamellae, extensive epithelial detachment and vascular congestion and dilation of lamellar capillaries and pooling of blood at 1 mg/l were observed. At 2.5 mg/l, epithelial hyperplasia, fusion of adjacent lamellae, obliteration of interlamellar spaces by means of tight junctions were also observed. Moreover, chloride cells proliferated along secondary lamellae, and mucus hypersecretion was evident. The overall results clearly indicate that gills are sensitive targets of TNT.